The Genus Butea Roxb. ex Willd. (Leguminosae-Papilionoideae) in Thailand - Sakuntala Ninkaew" (Science Faculty of Chiang Mai University, 2019)
A taxonomic revision of the genus Butea in Thailand is presented. Two species, B. monosperma and B. superba are enumerated. Key to species, descriptions, distributions and vernacular names are given. The habit, bark, the length of anthers, an outline and ridge of petiole, shape of epidermal cells on adaxial surface and crystal types are characteristics that could be complementary for species identification. But the pollen morphology is not taxonomically useful for identification at specific level.